Assessing the effectiveness of high‐profile targeted killings in the “war on terror”: a quasi‐experiment - Carson, Jennifer Varriale (Criminology & public policy, 2017)
Since the attacks of September 11, 2001, and the ensuing “war on terrorism,” the U.S. government has engaged in a series of controversial counterterrorism policies. Perhaps none is more so than the use of targeted killings aimed at eliminating the senior leadership of the global jihadist movement. Nevertheless, prior research has yet to establish that this type of tactic is effective, even among high‐profile targets. Employing a robust methodology, I find that these types of killings primarily yielded negligible effects.